Sistem Pendukung Keputusan Pemilihan Bidang Minat Program Studi Perguruan Tinggi Muhammadiyah di Provinsi Lampung Menggunakan Metode SAW - Erila Sari; M Abu jihad Plaza R (Politeknik Negeri Lhokseumawe, 2026)
Selecting a study program specialization at Muhammadiyah Higher Education institutions in Lampung Province is a crucial step for students in determining their academic expertise and future career prospects. However, students often face difficulties in choosing a concentration that aligns with their academic abilities and personal interests, frequently resulting in a mismatch of specialization. This research aims to develop a web-based Decision Support System (DSS) for selecting study program specializations using the Simple Additive Weighting (SAW) method. The Waterfall model is employed for system development, encompassing stages such as requirements analysis, system design, coding, and testing. The SAW method is applied to determine preference weights for each criterion, thereby ranking the best specialization alternatives based on prerequisite course grades and student interest questionnaires. The system is designed using PHP and a MySQL database to ensure flexible user accessibility. The research findings are expected to provide students with objective and accurate specialization recommendations, thereby minimizing decision-making errors. Furthermore, the system is intended to assist study programs within Muhammadiyah Higher Education institutions in Lampung Province in managing the distribution of student concentrations more systematically, objectively, and efficiently through an integrated digital platform.